2007
DOI: 10.1038/sj.onc.1210228
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression alterations are linked to tumorigenesis and non-neoplastic processes in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is known for its very poor overall prognosis. Accurate early diagnosis and new therapeutic modalities are therefore urgently needed. We used 377 feature microRNA (miRNA) arrays to investigate miRNA expression in normal pancreas, chronic pancreatitis, and PDAC tissues as well as PDAC-derived cell lines. A pancreatic miRNome was established comparing the data from normal pancreas with a reference set of 33 human tissues. The expression of miR-216 and -217 and lack of expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

33
528
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 622 publications
(569 citation statements)
references
References 39 publications
33
528
4
4
Order By: Relevance
“…Nine of the significantly differentially expressed miRNAs described by Bloomston et al 20 were also found in our study (miR-21, miR-100*, miR-143/miR-143*, miR-148a, miR-148a*, miR-205, miR-210, miR-222 and miR-375). Eleven of the significantly differentially expressed miRNAs described by Szafranska et al 21,26 were found in our study with very similar dm-values and fold change (miR-31, miR-130b, miR-143/miR-143*, miR-148a, miR-196b, miR-205, miR-210, miR-216, miR-217, miR-222/miR-222* and miR-375).…”
Section: Pancreatic Adenocarcinomas Vs Normal Pancreassupporting
confidence: 84%
See 4 more Smart Citations
“…Nine of the significantly differentially expressed miRNAs described by Bloomston et al 20 were also found in our study (miR-21, miR-100*, miR-143/miR-143*, miR-148a, miR-148a*, miR-205, miR-210, miR-222 and miR-375). Eleven of the significantly differentially expressed miRNAs described by Szafranska et al 21,26 were found in our study with very similar dm-values and fold change (miR-31, miR-130b, miR-143/miR-143*, miR-148a, miR-196b, miR-205, miR-210, miR-216, miR-217, miR-222/miR-222* and miR-375).…”
Section: Pancreatic Adenocarcinomas Vs Normal Pancreassupporting
confidence: 84%
“…All miRNAs either up-or down-regulated compared with normal pancreas in other studies 20,21,26 were also significantly differentially expressed in our study before the strict Bonferonni correction for multiple comparisons, except miR-155 that was not present in our microRNA array (Table 2).…”
Section: Pancreatic Adenocarcinomas Vs Normal Pancreassupporting
confidence: 56%
See 3 more Smart Citations